Graduate Students’ Perceptions of Young Teachers’ Influence on Classroom Climate: A Literature Review - Gurung, Sunita (BIC Journal of Management, 2025)
Classroom climate is one of the most significant factors in determining the learning environment of students in higher education. Teacher age and effectiveness, particularly regarding their first-time teacher status from students' perceptions, is a notably under researched but significant part of classroom dynamics. While young teachers bring energy, adaptability, and modern teaching approaches, student perceptions of their competence vary. While some students appreciate their approachability and creativity, others find fault in their experience, authority, and classroom management. The review examines the contribution of young teachers in influencing classroom climate in university, synthesizing recent evidence to draw attention to key factors shaping student opinion. Findings suggest that communication, institutional support, and instructional methods are essential to influence positive teacher-student interactions. By exploring the strengths and difficulties of young teachers, the study provides insights for universities, policymakers, and educationists on approaches to enhance teacher effectiveness and student engagement in higher education settings. The result shows that, although young teachers are highly engaged and innovative, professional institutional training seems to be essential for reducing gaps marked by age biases.